Plastic Pyrolisis of Low Density Polyethylene (LDPE) Using Bleaching Earth (BE) Catalyst Become Liquid Fuel - Abidin, Sri Widya Astuti; Nurmalasari, Nurmalasari; Sumiati, Sumiati; Ramadani, Ayu (Al-Kimia, 2020)
This study aims to determine the effect of adding Bleaching Earth (BE) catalyst to the amount of liquid fraction by pyrolysis of Low Density Polyethylene (LDPE) and find out the concentration of gasoline and diesel fractions from plastic pyrolysis Low density polyethylene (LDPE). The method in this study is the pyrolysis method (heating without oxygen) and analysis of the liquid fraction resulting from pyrolysis using GCMS (Gas Chromatrographic Mass Spectrometry). In this study, the effect of adding Bleaching Earth (BE) catalyst on Low Densiry Polyethylene plastic pyrolysis is the more catalyst used, the lower the quantity of liquid fraction. Based on GCMS analysis on plastic pyrolysis of Low Density Polyethylene (LDPE) from various variations of Bleaching Earth (BE) catalysts used the optimum concentration was obtained by adding 2.5 g, 5 g, and 7.5 g Bleaching Earth (BE) catalysts to produce fractions higher diesel (C13-C20), 37.04%, 31.04% and 35.59% respectively